Mobility and kinship in the world's first village societies - Pearson, J; Evans, J; Lamb, A; Baird, D; Hodder, I; Marciniak, A; Larsen, CS; Knüsel, CJ; Haddow, SD; Pilloud, MA; Bogaard, A; Fairbairn, A; et al. (National Academy of Sciences, 2023)
Around 10,000 y ago in southwest Asia, the cessation of a mobile lifestyle and the emergence of the first village communities during the Neolithic marked a fundamental change in human history. The first communities were small (tens to hundreds of individuals) but remained semisedentary. So-called megasites appeared soon after, occupied by thousands of more sedentary inhabitants. Accompanying this shift, the material culture and ancient ecological data indicate profound changes in economic and social behavior. A shift from residential to logistical mobility and increasing population size are clear and can be explained by either changes in fertility and/or aggregation of local groups. However, as sedentism increased, small early communities likely risked inbreeding without maintaining or establishing exogamous relationships typical of hunter-gatherers. Megasites, where large populations would have made endogamy sustainable, could have avoided this risk. To examine the role of kinship practices in the rise of megasites, we measured strontium and oxygen isotopes in tooth enamel from 99 individuals buried at Pınarbaşı, Boncuklu, and Çatalhöyük (Turkey) over 7,000 y. These sites are geographically proximate and, critically, span both early sedentary behaviors (Pınarbaşı and Boncuklu) and the rise of a local megasite (Çatalhöyük). Our data are consistent with the presence of only local individuals at Pınarbaşı and Boncuklu, whereas at Çatalhöyük, several nonlocals are present. The Çatalhöyük data stand in contrast to other megasites where bioarchaeological evidence has pointed to strict endogamy. These different kinship behaviors suggest that megasites may have arisen by employing unique, community-specific kinship practices.